KNOWING OBJECT LITERACY IN DEVELOPING CHILD LITERACY - Tyas, Ajeng Priendarning (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This study aims to collaborate theory with practice in the form of real events in the field. This study also describes the importance of literacy which is developed through the method of playing object literacy. This research can develop children's language patterns, especially those related to language skills and language skills that are applied in everyday life. The research method used is descriptive qualitative with literature in the form of photos, notes, and books. The result of this research is the lack of intensive communication and interaction with children. Although more than one child is not an obstacle to forming and developing language patterns, especially suitability and coherence with the object being observed. The researcher tries to provide a way of stimulating education with the object literacy method and the researcher starts with fairy tales using hand puppet media. This is what the researcher does with the auditory stage and in that way the child will try to record; starting from vocabulary, intonation, and structure. It is hoped that there will be changes in language skills, so that in the future children will be confident to develop more regular and complex language patterns.